Interpretation of Articles 1, 2 and 29 of the Convention on the Contract for the International Carriage of Goods by Road (CMR)in Case Law - Griškaitė, Viktorija; Dikčiūtė, Rūta (Vilnius University Open Series, 2024)
The CMR Convention applies to the carriage of goods by road. The first article of the Convention defines its scope. In order for the CMR Convention to apply to a contract for the carriage of goods by road, the carriage of goods must be carried in a vehicle for payment when the consignor and the consignee are in the territories of different State and when at least one of the parties to the contract is a member of this Convention. Even if shipments fall outside the scope of the CMR Convention, the parties may agree on the application of the Convention themselves, but this agreement must be clearly expressed. The second article of the CMR Convention adds that the Convention applies to all transport and in cases where a vehicle with cargo carries part of the road by sea, rail, inland waterway or air, but the cargo cannot be transshipped, which is very important when it is necessary to determine whether the Convention will apply to all or only part of the carriage. Article 29 of the CMR Convention indicates the conditions under which the carrier cannot use the provisions of the Convention regarding exemption from liability or limitation of liability. Intentional actions required for the application of Article 29 of the CMR Convention also include gross negligence and omission. The existence of objective and subjective criteria is necessary to establish awareness, which is required to prove actions caused by gross negligence, i.e., violation or non-observance of rules helping to ensure the safety of the cargo and deliberate actions or omissions, realizing that they may pose a threat to the cargo or increase the likelihood of its occurrence. However, it must be recognized that such actions or omissions of the carrier had a direct impact on the occurrence of damage to the cargo.